2014
DOI: 10.4172/2155-9880.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Ventricular Fibrillation by a Single Ectopic Beat in Three Dimensional Numerical Models of Ischemic Heart Disease: Abrupt Transition to Chaos

Abstract: Background: To explore the conditions most dangerous for the emergence of sustained Ventricular Tachycardia or Ventricular Fibrillation (VT/VF) a new computational model of ventricular myocardium including 2592 finite elements in three dimensions was created. Methods:The fully three dimensional model of right and left ventricular muscle was used to simulate the spread of electrical activation and the resulting electrocardiogram. Localized zones of ischemic muscle tissue were characterized by reduced conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…18 Given the chaotic and complex nature of VF-signals, which is also impacted by myocardial geometry, future studies with additional VFcharacteristics and advanced signal analysis techniques may provide valuable insights. 5,37 Secondly, VF-characteristics are studied to guide defibrillation during OHCA. Several previous studies showed an association between high AMSA and shock success, and an increase in AMSA following chest compressions.…”
Section: Discussionmentioning
confidence: 99%
“…18 Given the chaotic and complex nature of VF-signals, which is also impacted by myocardial geometry, future studies with additional VFcharacteristics and advanced signal analysis techniques may provide valuable insights. 5,37 Secondly, VF-characteristics are studied to guide defibrillation during OHCA. Several previous studies showed an association between high AMSA and shock success, and an increase in AMSA following chest compressions.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world chaotic and fractal systems span the spectrum from leaky faucets [3], to ferns [4], to heart rates [5][6][7], to cryptography [8,9]. Many scholars have studied the implications of nonlinearity, chaos and fractals for the social sciences, including sociology [10,11], urban studies [12][13][14][15][16], economics [17][18][19][20][21], architecture [22,23] and city planning [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Real-world chaotic and fractal systems span the spectrum from leaky faucets [3], to ferns [4], to heart rates [5][6][7], to cryptography [8,9]. Many scholars have studied the implications of nonlinearity, chaos and fractals for the social sciences, including sociology [10,11], urban studies [12][13][14][15][16], economics [17][18][19][20][21], architecture [22,23] and city planning [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%